Pleotropic role of RNA binding protein CELF2 in autophagy induction. Issue 8 (24th April 2019) - New, Jacob; Subramaniam, Dharmalingam; Ramalingam, Satish; Enders, Jonathan; Sayed, Afreen Asif Ali; Ponnurangam, Sivapriya; Standing, David; Ramamoorthy, Prabhu; O'Neil, Maura; Dixon, Dan A.; Saha, Subhrajit; Umar, Shahid; et al.
Abstract: We previously reported that ionizing radiation (IR) mediates cell death through the induction of CUGBP elav‐like family member 2 (CELF2), a tumor suppressor. CELF2 is an RNA binding protein that modulates mRNA stability and translation. Since IR induces autophagy, we hypothesized that CELF2 regulates autophagy‐mediated colorectal cancer (CRC) cell death. For clinical relevance, we determined CELF2 levels in The Cancer Genome Atlas (TCGA). Role of CELF2 in radiation response was carried out in CRC cell lines by immunoblotting, immunofluorescence, autophagic vacuole analyses, RNA stability assay, quantitative polymerase chain reaction and electron microscopy. In vivo studies were performed in a xenograft tumor model. TCGA analyses demonstrated that compared to normal tissue, CELF2 is expressed at significantly lower levels in CRC, and is associated with better overall 5‐year survival in patients receiving radiation. Mechanistically, CELF2 increased levels of critical components of the autophagy cascade including Beclin‐1, ATG5, and ATG12 by modulating mRNA stability. CELF2 also increased autophagic flux in CRC. IR significantly induced autophagy in CRC which correlates with increased levels of CELF2 and autophagy associated proteins. Silencing CELF2 with siRNA, mitigated IR induced autophagy. Moreover, knockdown of CELF2 in vivo conferred tumor resistance to IR. These studies elucidate an unrecognized role for CELF2 in inducing autophagy and potentiating the effects of radiotherapy in CRC.